Analyzing PAC's. - Resendez, Daniel (My University, 2013)
Political action committees have been the subject of controversial court cases and legislative reform. Judicial decisions and legislative reforms are the product of creating campaign finance aiming at the creation of a creating a competitive political environment. Today some of these rulings and reforms are considered troublesome and damaging to the political environment and they are the laws that gave birth to PACs. As it stands today, if a candidate receives support from a PAC and their opponent does not have PAC support, the candidate with PAC support tends to enjoy electoral success. This is examined through a case study focusing on Oklahoma elections.
Keywords: Political action committees; Political action committees; Campaigns; Elections; PACs; Political Action Committees